2020
DOI: 10.1177/0273475320950015
|View full text |Cite
|
Sign up to set email alerts
|

Running With Your Hair on Fire: Lessons Learned From Transitioning a National University Sales Competition From Face-to-Face to Virtual in 16 Days

Abstract: Since their inception, university sales competitions have been key learning and educational components of university sales education. Over the past two decades, the oldest and one of the largest sales competitions in the United States has been held in a face-to-face format. However, due to the educational environment created from the COVID-19 pandemic, this competition was forced to convert to a virtual format over a 16-day period. This research outlines the steps taken to convert this event to virtual format … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Empirical research has shown that salesperson anxiety, including sales role-plays, leads to poor communication and performance (Erevelles & Fukawa, 2013). If the level of anxiety is moderate or high, students may develop an apprehension that can lead to low performance (Inks et al, 2020). The existence of apprehension among sales students makes it difficult to properly gauge the selling scenario and the buyer's behavior.…”
Section: Anxiety and Sales Role-playsmentioning
confidence: 99%
See 4 more Smart Citations
“…Empirical research has shown that salesperson anxiety, including sales role-plays, leads to poor communication and performance (Erevelles & Fukawa, 2013). If the level of anxiety is moderate or high, students may develop an apprehension that can lead to low performance (Inks et al, 2020). The existence of apprehension among sales students makes it difficult to properly gauge the selling scenario and the buyer's behavior.…”
Section: Anxiety and Sales Role-playsmentioning
confidence: 99%
“…Although some research exists examining factors that contribute to the creation of anxiety in virtual education, missing is research that investigates how abrupt crisis and resulting levels of anxiety affect students and the effectiveness of virtual education and role-plays (Inks et al, 2020). Specific to our study, we assessed the virtual learning experience with regard to class preparation, class learning, satisfaction with the experience, and ITPSC.…”
Section: Anxiety and Covid-19mentioning
confidence: 99%
See 3 more Smart Citations